1984
DOI: 10.1172/jci111328
|View full text |Cite
|
Sign up to set email alerts
|

New avian model of experimental glomerulonephritis consistent with mediation by cellular immunity. Nonhumorally mediated glomerulonephritis in chickens.

Abstract: Astract. The present study examined the role of cell-mediated immunity (CMI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
90
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 33 publications
(27 reference statements)
1
90
0
Order By: Relevance
“…For measurement of IFN-␥ mRNA by real-time PCR, 1 g of RNA (n ϭ 6 to 7 for each group with GN) was treated with 1 unit of amplification-grade DNase I (Invitrogen) then primed with 500 ng of Oligo(dT) [12][13][14][15][16][17][18] (Roche, Mannheim, Germany) and reverse transcribed (Super Script II; Invitrogen). Gene-specific primers for murine IFN-␥ and murine ␤-actin were designed (Vector NTI software; Invitrogen).…”
Section: Assessment Of Il-18 In Nephritic Kidneysmentioning
confidence: 99%
See 1 more Smart Citation
“…For measurement of IFN-␥ mRNA by real-time PCR, 1 g of RNA (n ϭ 6 to 7 for each group with GN) was treated with 1 unit of amplification-grade DNase I (Invitrogen) then primed with 500 ng of Oligo(dT) [12][13][14][15][16][17][18] (Roche, Mannheim, Germany) and reverse transcribed (Super Script II; Invitrogen). Gene-specific primers for murine IFN-␥ and murine ␤-actin were designed (Vector NTI software; Invitrogen).…”
Section: Assessment Of Il-18 In Nephritic Kidneysmentioning
confidence: 99%
“…Severe crescentic glomerular injury is Th1 directed, effector CD4ϩ cell mediated (6,7), and regulated by endogenous and exogenous Th2 cytokines IL-4 and IL-10 (8 -10). Although it is clear that humoral immune mediators are capable of inducing injury (11,12), crescent formation can occur in the absence of autologous antibody (13)(14)(15).…”
mentioning
confidence: 99%
“…After deposition of rabbit gammaglobulin in rat glomeruli, adoptive transfer of antigen-specific syngeneic T cells can elicit GN. 2 Bolton et al, 4 using neonatally bursectomized chickens, also directly demonstrated a role for cell-mediated immunity in the development of nephritis. Most recently, Radeke et al 10 demonstrated that appropriate phenotypes of clonotypic T cells can elicit proteinuria in immunodeficient mice, if specific antigen accumulates within the glomerular mesangium prior to the adoptive transfer of the effector/memory cells.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] T cells clearly modulate antibody responses to T-dependent antigens, and the resulting antibodies can contribute to immune complex-mediated glomerulonephritis (GN). 1,2 Moreover, Tipping et al 8 reported that macrophage accumulation in experimental anti-glomerular basement membrane antibodyinduced GN is preceded by T-cell accumulation.…”
mentioning
confidence: 99%
“…Anti-GBM GN has been studied in a number of animal models using immunizations with heterologous or homologous GBM preparations or a3IV-NC1 to breach tolerance against the autoantigen, often referred to as experimental autoimmune GN (EAG) (10)(11)(12)(13). We have previously characterized the T cell response to heterologous human a3IV-NC1 in DBA/1 mice and found a biphasic disease course.…”
mentioning
confidence: 99%